2002
DOI: 10.1124/mol.62.6.1306
|View full text |Cite
|
Sign up to set email alerts
|

11β-Hydroxyprogesterone Acts as a Mineralocorticoid Agonist in Stimulating Na+Absorption in Mammalian Principal Cortical Collecting Duct Cells

Abstract: The binding of mineralocorticoid hormones to the mineralocorticoid receptor is the first step in a cascade of events leading to the stimulation of Na ϩ reabsorption by renal cortical collecting duct (CCD) principal cells. The agonist properties of mineralocorticoid hormones are linked to contacts between their 21-hydroxyl group and Asn770, a residue of the ligand-binding domain of the human mineralocorticoid receptor (hMR). Here, we investigate whether the presence of a hydroxyl group at position 11, 17, or 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…Luciferase activity weakly increased in response to 10 Ϫ6 M dexamethasone, but this stimulation was 2.5-fold lower than that produced by 10 Ϫ6 M aldosterone ( Figure 8A), suggesting that the MR rather than the GR mediates aldosterone-induced NF-B activation. In agreement with this hypothesis, the progesterone derivative 17-␣-hydroxyprogesterone, that specifically antagonizes MR transactivation without significantly altering GR activity 23 (unpublished data; see the Concise Methods section) also fully prevented the effect of 10 Ϫ6 M aldosterone on NF-B-dependent gene transcription ( Figure 8B). Moreover, siRNA targeting the MR, which decreased MR abundance by 70% without altering GR expression ( Figure 8C), prevented aldosterone-induced IB␣, IL-6, and PAI-1 mRNA expression ( Figure 8D), whereas effective knockdown of the GR did not ( Figure 9, A and B).…”
Section: Mr But Not Glucocorticoid Receptor Is Required For Aldosterosupporting
confidence: 64%
See 1 more Smart Citation
“…Luciferase activity weakly increased in response to 10 Ϫ6 M dexamethasone, but this stimulation was 2.5-fold lower than that produced by 10 Ϫ6 M aldosterone ( Figure 8A), suggesting that the MR rather than the GR mediates aldosterone-induced NF-B activation. In agreement with this hypothesis, the progesterone derivative 17-␣-hydroxyprogesterone, that specifically antagonizes MR transactivation without significantly altering GR activity 23 (unpublished data; see the Concise Methods section) also fully prevented the effect of 10 Ϫ6 M aldosterone on NF-B-dependent gene transcription ( Figure 8B). Moreover, siRNA targeting the MR, which decreased MR abundance by 70% without altering GR expression ( Figure 8C), prevented aldosterone-induced IB␣, IL-6, and PAI-1 mRNA expression ( Figure 8D), whereas effective knockdown of the GR did not ( Figure 9, A and B).…”
Section: Mr But Not Glucocorticoid Receptor Is Required For Aldosterosupporting
confidence: 64%
“…In all experiments using one or more of these compounds, control cells were incubated in the presence of the same concentration of DMSO as treated cells. As shown by RafestinOblin et al, 23 17OHP behaves as a competitive inhibitor of the MR and was shown to antagonize up to 80% of aldosterone-induced transactivation activity of the MR. 17OHP also attenuated the aldosteronestimulated amiloride-sensitive short-circuit current in murine mpkCCD cl4 cells. In addition, 17OHP is a weak agonist/antagonist of the GR because the GR transactivation activity induced by 10 Ϫ6 M 17OHP amounted to approximately 15% of that induced by 10…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…This is the case, for instance, of progesterone, the antagonist activity of which has been linked to its inability to establish contact with the Asn770 residue of MR-LBD . Two progesterone derivatives, 17␣-and 20␣-hydroxyprogesterone (but not 11␤-hydroxyprogesterone) act as potent MR antagonists and inhibit the aldosterone-stimulated absorption of Na ϩ in cultured mouse mpkCCD cl4 collecting duct principal cells (Rafestin-Oblin et al, 2002). Rossier et al (1980) first reported that testosterone (T) specifically displaces [ 3 H]aldosterone from its nuclear and cytoplasmic binding sites and antagonizes the stimulating action of aldosterone on Na ϩ transport in the toad bladder.…”
mentioning
confidence: 99%
“…In this study, the ability of the two main natural androgens, T and its active metabolite dihydrotestosterone (DHT), and the potent synthetic steroidal AR agonist methyltrienolone (R1881) to modulate Na ϩ absorption was analyzed using the short-circuit current (I sc ) method in cultured mpkCCD cl4 collecting duct cells, which had retained the main features of intact CCDs, including a Na ϩ transport mechanism that was stimulated by aldosterone (Bens et al, 1999;Rafestin-Oblin et al, 2002). The ability of T, DHT, and R1881 to activate or inactivate MR was investigated in cis-trans cotransfection assays in HEK 293T and COS-7 cells.…”
mentioning
confidence: 99%
“…Thr739 is the last residue in helix-11 whose mutation to alanine has no effect on the binding of triamcinolone acetonide, but does result in a 16-fold reduction in transactivation (Lind et al, 2000). In addition to these mutation studies, as discussed already, there is also overwhelming evidence across the family to support the hypothesis that Asn564 is crucial for the agonistic activity of GR and related receptors (Bledsoe et al, 2005;Bledsoe, Stewart, and Pearce, 2004;Fagart et al, 1998;Hellal-Levy et al, 2000;Necela and Cidlowski, 2003;Rafestin-Oblin et al, 2002). The role of Asn564 (Asn705 in AR, Asn770 in MR) was previously discussed.…”
Section: Modulate the End Of Helix-11 And The Loop Between Helices-11 Andmentioning
confidence: 88%